Electrical impedance tomography to aid in the identification of hypoxemia etiology: Massive atelectasis or pneumothorax? A case report - Zhou, Runshi; He, Chaokai; Chi, Yi; Yuan, Siyi; Tang, Bo; Li, Zunzhu; Li, Qi; He, Huaiwu; Long, Yun (Frontiers in Medicine, 2022)
Background: Bedside ultrasound is often used to determine the etiology of hypoxaemia, but not always with definitive results. This case reports the application of electrical impedance tomography (EIT) and saline injection to determine the etiology of hypoxaemia in a complex case that could not be identified by bedside ultrasound. The determination of the etiology of hypoxaemia by EIT and saline injection, regional ventilation and perfusion information can be used as a new clinical diagnostic method. Case presentation: A post-cardiac surgery patient under prolonged mechanical ventilation for lung emphysema developed sudden hypoxemia in the intensive care unit (ICU). A line pattern and lung sliding abolishment were found in the left lung, but there was no evidence of a lung point on bedside ultrasound. Hence, the initial diagnosis was considered to be a massive pneumothorax. To further define the etiology, EIT and saline embolism were used to assess regional ventilation and perfusion. A massive ventilation defect was found in the left lung, in which regional perfusion was maintained, resulting in an intrapulmonary shunt in the left lung. Finally, the conjecture of a pneumothorax was ruled out considering the massive atelectasis. After the diagnosis was clarified, hypoxaemia was corrected by restorative ventilation of the left lung after changing the patient's posture and enhancing sputum drainage with chest physiotherapy. Conclusions: This was the first clinical case involving EIT and saline bolus to establish the differential diagnosis and guide clinical decisions for patients with acute hypoxemia. This study highlighted that combination regional ventilation, EIT perfusion, and saline bolus provided helpful information for determining the etiology of hypoxemia. The results of this study contribute to the development of emergency patient management.